1977
DOI: 10.1002/ejsp.2420070304
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, vicarious reinforcement and extraversion on blood donating in adults: Immediate and long‐term effects

Abstract: Studied the immediate and long-term effects of modeling on adult altruism using a quasi field experiment in a naturalistic setting. Forty-three female trainee occupational therapists aged 18-21 observed or did not observe a female model volunteer to donate blood. Modeling significantly increased the number of female observers who (a) also agreed to donate and (b) in turn actually gave their blood. The opportunity to donate blood occurred in a naturalistic situation on average six weeks after the commitment, It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…For example, Bryan and Test (1967) conducted a series of experiments and found that individual's helping behaviors significantly increase when others model helping behavior. Similarly, Rushton and Campbell (1977) found that individuals were more likely to donate blood after viewing others donate.…”
Section: Pro-social Modelingmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Bryan and Test (1967) conducted a series of experiments and found that individual's helping behaviors significantly increase when others model helping behavior. Similarly, Rushton and Campbell (1977) found that individuals were more likely to donate blood after viewing others donate.…”
Section: Pro-social Modelingmentioning
confidence: 93%
“…Elementary school students (N = 416) Examined factors that influence student bystanders in bullying situations Rushton and Campbell (1977) Female trainee occupational therapists (N = 43) Norms around gender are also an important factor related to bystander intervention. Eagly and Crowley's (1986) meta-analysis of gender and helping behavior established that gender role beliefs are related to different prosocial behaviors for men and women.…”
Section: Mcmahon (2010)mentioning
confidence: 99%
“…Either observing a positive role model donating or knowing people who already donate has been shown to lead to an increase in the number of future donations in first-time donors (Rushton & Campbell, 1977). Either observing a positive role model donating or knowing people who already donate has been shown to lead to an increase in the number of future donations in first-time donors (Rushton & Campbell, 1977).…”
Section: Reinyoorcementmentioning
confidence: 99%
“…Those in the pre-contemplative stage would be non-donors and would benefit from consciousness raising techniques such as education about how blood donation works and where the products are used (e.g. Rushton & Campbell, 1977). The consciousness raising may move such non-donors to the contemplative stage.…”
Section: The Transtheoretical Model Of Behavioural Changementioning
confidence: 99%
“…Help also is more likely to be given when the potential help-giver is not in a hurry (Darley & Batson, 1973), when salient models behave in a help-giving manner (Bandura, 1973;Piliavin, Rodin, & Piliavin, 1969;Rushton & Campbell, 1977), and when the benefits relative to the costs o f helping are high (Hatfield, Walster, & Piliavin, 1978).…”
Section: S Itu a Tio N A L Determ Inants O F Helping Behaviourmentioning
confidence: 99%